The economics of imperfect labor markets - Boeri, Tito (Book collections on Project MUSE., 2008)
Most labor economics textbooks pay little attention to actual labor markets, with the exception of the occasional reference to competitive labor markets like that of the United States. The Economics of Imperfect Labor Markets is the only textbook to focus on imperfectly competitive labor markets and to provide a systematic framework for analyzing how labor institutions function and interact in these markets. The Economics of Imperfect Labor Markets examines the many institutions that affect the behavior of workers and employers in imperfect labor markets. These include minimum wages, employmen.